Condiciones de vida y estrategias de afrontamiento de las mujeres con cáncer de mama en Córdoba, Colombia - Ruiz Doria, Sixta Carolina; Valencia Jimenez, Nydia Nina; Ortega Montes, Jorge Eliecer (Anales de Psicología / Annals of Psychology, 2020)
Breast cancer is a reality that has meant death for thousands of women, constituting a stressful event that affects the emotional and psychological health of the patient. This study aims to determine the types of coping strategies developed by women diagnosed with breast cancer in the city of Monteria, Colombia in the period 2013-2017. A sample of 131 patients was determined and a probability of success and failure of 50% was estimated, an error no greater than 5% and a confidence of Zα = 95%. The sociodemographic survey showed that the participants are of limited economic resources, low educational level, unemployed, with sentimental partner and profess the catholic religion; the data provided by the Inventory Brief-COPE-28 refer to the preference for the type and strategy of active coping in 67.3% and 83.78% respectively, in the frequency of use of the strategy was obtained the planning (55%), active (56 %) and religion (64%); and the level of regular coping prevailed in all categories. Despite the precarious living conditions, the participants use active strategies to survive, which implies that integral accompaniment processes must be implemented that enhance the coping capacity of the subjects.